THE ETYMOLOGY OF THE WORD “MOTHER” IN UZBEK AND ENGLISH LANGUAGES - Khashimova Jeren Beshim kizi (Modern American Journals, 2025)
This research explores the etymology and linguistic development of the word “mother” in both English and Uzbek languages, offering a comparative analysis of their historical roots, phonetic evolution, and cultural significance. This comparative etymological study not only illustrates the divergent linguistic lineages of English and Uzbek but also highlights universal patterns in language, such as the early development and emotional centrality of familial terms like “mother”. The research contributes to a broader understanding of language evolution and cultural perspectives embedded in linguistic expressions.
Keywords: nurturer, symbolic representations, caretaker, flawed individuals, sacrifice, compelling.